Sintasan dan Pertumbuhan Larva Ikan Gabus (Channa striata) Diberi Artemia yang Diperkaya Vitamin A - Junius Akbar (Program of Biology Education, Universitas Lambung Mangkurat, 2022)
The survival rate of snakehead fish (Channa striata) is low. Provision of natural food during the survival phase and growth of snakehead fish larvae is very important. Artemia is a natural food for freshwater and marine fish larvae which has high nutritional value, but lacks vitamin A. Enrichment techniques are needed to increase the nutritional value of Artemia. The aim of this study was to compare survival rates, growth rates of snakehead fish larvae fed Artemia feed enriched with vitamin A. Snakehead fish were reared for 16 days and given Artemia enriched with vitamin A (with 1,000 IU/L, 2,000 IU/L, and 3,000 IU/l. The results showed that treatment had no significant effect on survival rate (58.33-98.33%), but had a significant effect (P>0.05) on total weight growth and feed conversion ratio (1.062-4.23 gram and 3.581- 5.100 grams), and had a very significant effect (P>0.01) on total length growth (1.036-1.256 cm). The best dose for maintenance of snakehead fish larvae is Artemia enriched with vitamin A with 3,000 IU/L.